Recent advances in antibody-inducing poxviral and adenoviral vectored vaccine delivery platforms for difficult disease targets. - de Cassan, S; Draper, S (2013)
Viral vectored vaccine delivery platforms have traditionally been used for the induction of cellular rather than humoral immunity. However, in recent years, recombinant adenoviral and poxviral vectored vaccines have been optimized to induce B-cell responses, resulting in the demonstration of high-titer antibody responses in a wide variety of animal species. These approaches have now been translated, confirming the induction of substantial levels of antigen-specific IgG in a series of Phase I human clinical trials targeting HIV-1 and Plasmodium falciparum malaria. To further improve the induction of antibodies, mixed-modality regimens based on recombinant viral and protein/adjuvant vaccines are now being assessed. However, limited data exist about the underlying mechanisms mediating the induction of B-cell responses by these subunit vaccines and their ability to influence the qualitative aspects of vaccine-induced B-cell populations and immunoglobulin. Future studies in this area are needed to guide the rational design of antibody-inducing subunit vaccine strategies.